Cellulose nanofiber-multilayered fruit peel-mimetic gelatin hydrogel microcapsules for micropackaging of bioactive ingredients. (1st February 2020) - Seo, Mintae; Seo, Minjeong; Choi, Song-Ee; Shin, Kyounghee; Lee, Jun Bae; Yang, Dong-Yeon; Kim, Jin Woong
Highlights: A cellulose-multilayered fruit peel-mimetic microcapsule (FPMC) system is proposed as a new micropackaging technology. Fruit peel biomimicry was accomplished by coating the gelatin core flesh with a cellulose-reinforced shell containing an antioxidant and an oil softener. Tailored engineering of the FPMC shell prevented generation of microcracks during drying, thus exhibiting improved antioxidation performance. Abstract: We report a facile but robust approach to fabricate fruit peel-mimetic microcapsules (FPMCs) of which shell was structured by layering cellulose nanofibers (CNFs) with an antioxidant and a waxy compound on monodisperse gelatin microparticles using the layer-by-layer deposition. The thickness and moduli of the shell increased commonly depending on the number of CNF layers, indicating that the incorporation of CNFs made the shell layer rigid. We determined that the coating of the outermost FPMC layer with dodecane nanoemulsions softened the shell surface, thus preventing the generation of microcracks, which is essential for minimizing dehydration in the drying process. Furthermore, we also confirmed that the co-deposition of a phenolic compound, gallic acid, which is encapsulated in the polymeric micelles, with the shell layers allowed the FPMCs to exert antioxidant effects against the influx of oxygen from the atmosphere. These results highlight that our FPMC system could pave the way for the development of a micropackaging technology that enables encapsulation and stabilization of bioactive ingredients.